Routing for Mobile UWSN: A Survey - Priyalakshmi, B; Mahalakshmi, K (International Journal of Engineering and Technology, 2018)
Recently Underwater Wireless Sensor Networks (UWSNs) is now emerging as a important research area to explore underwater environments and its resource. Underwater wireless senor nodes are utilized for extensive variety of uses, for example, checking the marine condition for scientific to commercial investigation and coastline surveillance to underwater contamination observing, from water-based calamity preventions to water-based games facilitation. Due to the unstable underwater environment there is a need to increase the scalability and reduce the energy consumption. Connectivity and Coverage are the important properties that decide the proper detection and communication in UWSN. Many researchers have introduced the routing protocol which deals with mobility of node but the research investigation needs further advancement to model a powerful routing algorithm which control movement of the node. In this paper the literature survey on different routing protocol for mobile UWSN are discussed.Â Â